The CTX-M-15-producing Escherichia coli clone O25b: H4-ST131 has high intestine colonization and urinary tract infection abilities. - Sophie Vimont; Anders Boyd; Alexandre Bleibtreu; Marcelle Bens; Jean-Michel Goujon; Louis Garry; Olivier Clermont; Erick Denamur; Guillaume Arlet; Alain Vandewalle (PLoS ONE, 2012)
Increasing numbers of pyelonephritis-associated uropathogenic Escherichia coli (UPEC) are exhibiting high resistance to antibiotic therapy. They include a particular clonal group, the CTX-M-15-producing O25b:H4-ST131 clone, which has been shown to have a high dissemination potential. Here we show that a representative isolate of this E. coli clone, referred to as TN03, has enhanced metabolic capacities, acts as a potent intestine- colonizing strain, and displays the typical features of UPEC strains. In a modified streptomycin-treated mouse model of intestinal colonization where streptomycin was stopped 5 days before inoculation, we show that TN03 outcompetes the commensal E. coli strains K-12 MG1655, IAI1, and ED1a at days 1 and 7. Using an experimental model of ascending UTI in C3H/HeN mice, we then show that TN03 colonized the urinary tract. One week after the transurethral inoculation of the TN03 isolates, the bacterial loads in the bladder and kidneys were significantly greater than those of two other UPEC strains (CFT073 and HT7) belonging to the same B2 phylogenetic group. The differences in bacterial loads did not seem to be directly linked to differences in the inflammatory response, since the intrarenal expression of chemokines and cytokines and the number of polymorphonuclear neutrophils attracted to the site of inflammation was the same in kidneys colonized by TN03, CFT073, or HT7. Lastly, we show that in vitro TN03 has a high maximum growth rate in both complex (Luria-Bertani and human urine) and minimum media. In conclusion, our findings indicate that TN03 is a potent UPEC strain that colonizes the intestinal tract and may persist in the kidneys of infected hosts.